2022
DOI: 10.12962/j20861206.v37i1.12602
|View full text |Cite
|
Sign up to set email alerts
|

Shear Behaviour Analysis of Reinforced Concrete Beam Using Non-Linear Finite Element Simulation

Abstract: This paper investigates shear behaviour of reinforced concrete using multi-surface plasticity model. This analysis uses nonlinear finite element simulation using 3D-NLFEA finite element package. The experimental data adopted from the results of experimental test on eighteen beams where nine beams carried out by Bresler and Scordelis in 1963 and similar nine beams carried out by Vecchio and Shim in 2004. The constitutive model for the concrete material which used in this simulation is based on the plasticity-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, electrodeposition allows film formation directly on the substrates and supports the integration of the prepared film within the device [2,3]. Previous studies on the electrodeposition of Cu 2 O [4][5][6][7], which is known as a robust, facile, and scalable technique, have shown that surface features and microstructure the deposit be tuned by adjusting reaction conditions [8]. These copper oxide compounds are considered as a promising low-cost semiconductor material for photocatalyst application.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, electrodeposition allows film formation directly on the substrates and supports the integration of the prepared film within the device [2,3]. Previous studies on the electrodeposition of Cu 2 O [4][5][6][7], which is known as a robust, facile, and scalable technique, have shown that surface features and microstructure the deposit be tuned by adjusting reaction conditions [8]. These copper oxide compounds are considered as a promising low-cost semiconductor material for photocatalyst application.…”
Section: Introductionmentioning
confidence: 99%